Changes in mental health levels among Chinese athletes from 1995 to 2023 - Xi, Yue; Liu, Fengbo; Yang, Jian (Frontiers in Psychology, 2024)
Objective In recent years, with the increasing intensity of sports competition and social pressure, the issue of mental health among athletes have gradually attracted attention. Understanding the changing trends of athletes’ mental health is of great significance for formulating effective intervention measures and safeguarding the mental health of athletes. Methods A total of 306 articles were accumulated from September to November 2023 by selecting literature from databases that measured the mental health of Chinese athletes using the Symptom Checklist-90 (SCL-90). Based on the screening criteria, 28 articles (N = 4,227) were finally included. A cross-sectional historical meta-analysis of these 28 studies using the SCL-90 between 1995 and 2023 was conducted. Based on cross-sectional historical meta-analysis methods, specific statistical methods, such as correlation and regression analyses, were used to examine trends over time in the scores of the nine SCL-90 factors measured by the athletes in the studies, as well as athlete type and gender differences. Results (1) Athletes’ scores on the depression, hostility, phobic anxiety, and paranoid ideation factors gradually increased with the change of era, and the explanation rate of the variation of each factor by era ranged from 18.8 to 27.2%; (2) During the period from 1995 to 2023, the mental health of athletes in China gradually deteriorated on the factors of depression, hostility, and phobic anxiety, the rate of change was rapid, with a medium to large magnitude (0.28–0.42); (3) The scores of female athletes on the depression and psychoticism factors scores showed a significant upward trend, while male mental health scores for each factor did not improve significantly over the years; (4) College athletes’ scores on the depression, anxiety, hostility, phobic anxiety, paranoid ideation, and psychoticism factors showed an upward trend as the years changed. Conclusion Chinese athletes’ mental health has been on a downward trend for the past 28 years, which needs to be a cause for concern.